Relational turbulence and health‐compromising behaviors: Integrating relational turbulence and stress theories. Issue 4 (12th November 2020) - Weigel, Daniel J.; Shrout, M. Rosie
Abstract: This study drew upon key elements of relational turbulence and stress and coping theories to advance a conceptual model linking relational turbulence with stress, depression, and involvement in health‐compromising behavior, such as drug and alcohol use, limited or extreme physical activity, disordered eating patterns, and unprotected sex. Romantically involved individuals (N = 476) completed an online survey. Structural equation modeling revealed that greater relational turbulence was related to higher perceived stress and depression which, in turn, were related to more frequent engagement in health‐compromising health behavior. The study provides an extension to both the relational turbulence and health literatures by identifying the downstream effects of relational turbulence on psychological and behavioral health.